Propriedades elétricas de materiais híbridos de Sílica/orgânico à base de GPTS/TEOS preparados pelo método sol-gel - Monteiro, Daniela Aparecida [UNESP] (2015)
Organic/silica hybrid materials also known as Organically Modified Silicates (ORMOSIL) have been object of study due to the diversity of organically functionalized silicon alcoxides with organic groups covalently bonded to the silicon (epoxy, vinyl, amino, phenyl, etc). This work aims the study of the electrical properties of the organic/silica hybrid materials prepared by sol-gel technique derived from the acid hydrolysis of 3- glycidoxypropyltrimethoxysilane (GPTS) and tetraethylorthosilicate (TEOS). Organic/silica hybrid films were deposited on glass substrates by dip-coating technique and sandwiched between gold electrodes to allow the impedance spectroscopy measurements. The study was carried out on film samples with different GPTS/TEOS molar ratio and films submitted to different thermal treatments for densification. Also impedance spectroscopy measurements were performed at different temperatures for samples with different GPTS/TEOS molar ratio. It was determined regarding the increase of the GPTS concentration in the hybrid matrix that the conductivity increases from 8.74x10- 10 S/cm to 8.04x10-9 S/cm for films GT(1:1) and GT(7:1), respectively. The transport mechanism involves H+ ions transfer protonic charge to the oxygen of epoxy groups, and this transport mechanism is described by Grotthuss model. The activation energy decreases with the increase of the increase of the GPTS concentration, being 0.83 eV and 0.54 eV and for the GT (3: 1) and GT (7: 1), respectively. Therefore, the concentration of GPTS, promotes the mobility of carriers in the matrix, and also the number of charge carriers present in the catalyst solution increases proportionately with the increase in the molar ratio of GPTS. The thermal treatment for densification promotes elimination of pores in the hybrid matrix favoring the mobility of charge carriers increasing the conductivity of the hybrid material. Key-words: sol-gel; organic/silica hybrid; electrical ...